Pengaruh Fasilitas dan Lokasi Terhadap Tingkat Kepuasan Konsumen Coffee Shop Pada “Tell Kopi Kediri” - Permada, Agil Reczy Tegar; Maheri L, Sonny Subroto; Akbar, Taufik (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The aim of this research is to explain the partial influence of facility and location variables on the level of consumer satisfaction. The population in this study were all TELL KOPI Kediri café consumers. The sampling technique uses the Nonprobability Sampling method using purposive sampling. The results of the research show that the facility and location variables have a partial effect on consumer satisfaction, this can be seen from the facility variable (X1) with a sig value of 0.000 < 0.05 and the calculated t value (7.940) > t table value (1.661), and the variable location (X2) with a sig value of 0.000 < 0.05 and the calculated t value (2.643) > t table value (1.661). Simultaneously the facility (X1) and location (X2) variables can be seen with a sig value of 0.000 < 0.05 and the calculated F value (32.022) > F ¬table (3.090)